The Damage I Have Done to Myself: Physical Intelligence Among College Athletes - Nelson, Mariah Burton (Journal of Intercollegiate Sport, 2009)
Thirty years after graduating from Stanford University, I look back on my experience as a star college basketball player and marvel: Why and how did I damage both knees so severely that it is now impossible to walk downstairs without limping? Is lifelong disability an inevitable consequence of college sports? Whose responsibility is it to ensure that college athletes not only learn how to stretch and push their bodies, but also how to care for them? In this article, I describe what I call physical intelligence (the ability to listen to the body’s subtle signals and respond wisely to them). I call on college coaches and athletic trainers to advocate openly for physical intelligence education and the long-term health of their athletes, even if such advocacy results in fewer team victories. I assert that the ultimate responsibility for the health of college athletes rests in the hands of the athletes themselves, who can develop physical intelligence the way they develop sports skills—that is, through practice.